Managing conflict in semi-military public organizations: the role of emotional intelligence, digital communication skills, mindfulness, and resilience - Yusmedi Nurfaizal; Zaenal Khafidin (BISMA (Bisnis dan Manajemen), 2026)
This study examines the influence of emotional intelligence and digital communication competence on conflict management styles in semi-military public organizations, with workplace mindfulness as a mediator and psychological resilience as a moderator. A quantitative survey was conducted among Civil Service Police Unit officers in four regencies in Central Java from February to March 2025. Data were analyzed using Partial Least Squares Structural Equation Modeling. The findings show that emotional intelligence and digital communication competence significantly affect conflict management styles, both directly and indirectly via workplace mindfulness. Psychological resilience strengthens the positive relationship between mindfulness and conflict behavior. These results emphasize the need to develop integrated competencies in emotional regulation, digital communication, and mental resilience. The study contributes a moderated mediation model relevant to hierarchical and high-stress public organizations, with implications for competency-based training and HR policies in Indonesia’s decentralized governance context.